Impact of respiratory virus infection in patients with chronic chest disease. - Wiselka, M. J. (Cambridge University Press, 1993)
This study investigated the morbidity associated with respiratory virus infections in patients with well-documented chest disease, and the risk of transmission between close contacts. Patients informed the study team if they were exposed to a family member or colleague with a cold. Patients and symptomatic index cases recorded respiratory symptoms during the study period. Acute nasopharyngeal swabs and paired sera were obtained for viral diagnosis. Twenty-five (43%) of 58 recorded exposures resulted in a symptomatic illness and 16 (28%) patients developed lower respiratory tract symptoms. Sixteen (64%) of the 25 symptomatic patients contacted their general practitioner, 14 (56%) received antibiotics and 4 (16%) were hospitalized. Mean duration of illness was 10.6 days in symptomatic patients and 5.7 days in their corresponding index cases (P < 0.005). Mean symptom scores were 100.6 in symptomatic patients and 62.2 in index cases (P < 0.01). Respiratory viruses were identified in 19 (33%) episodes. Rhinovirus, coronavirus and respiratory syncytial virus infections were all associated with lower respiratory tract exacerbations. Respiratory tract symptoms following exposure to a cold were comparatively severe in these patients with chronic chest disease. This group of patients might gain particular benefit from the introduction of effective vaccines or antiviral therapy.